Unreal game development - Amresh, Ashish; Okita, Alex; Taylor and Francis (Boca Raton, FL : A K Peters/CRC Press, an imprint of Taylor and Francis, 2010)
Using Unreal Engine 3, the authors teach aspiring game makers the fundamentals of designing a computer game. The only prerequisite is a basic working knowledge of computers and a desire to build an original game. To get the most out of the book, the authors recommend gathering up some friends and working through the book together as a team and with time limits, mimicking the key elements of real world commercial game development.
chapter Part I: Design -- chapter Part II: Art The Tool Box of the Unreal Artist: More Than Spanners and Wrenches -- chapter Part III: Programming.
Keywords: Computer games -- Programming; UnrealScript (Computer program language); GAMES -- Board